Wage determination, taxes, and employment: evidence from Finland - Timo Tyrväinen (Bank of Finland, 1995)
12 1 Introduction 13 2 Cointegration and error correction 17 2.1 An attractor 17 2.2 Cointegrating relations and error correction equations 19 3 Unions and wage bargaining 20 3.1 Union objectives 21 3.2 The bargaining procedure 22 3.3 Local wage setting 24 3.4 Centralized vs. decentralized bargaining 24 4 Extensions to the 'standard bargaining model' 28 5 Empirical evidence 31 5.1 The role of firm- and industry-specific factors 32 5.2 Wage adjustment and (un)employment 33 5.3 Real wage resistance 35 5.4 Earlier evidence on wage setting in Finland 37 6 Summaries of the chapters 41 6.1 Tax incidence in union models (Chapter 2) 41 6.2 Unions, wages and employment (Chapter 3) 44 6.3 Wage Setting, Taxes and Demand for Labour (Chapter 4) 45 6.4 Wage drift and error correction (Chapter 5) 47 References 49 Tiivistelmä: The purpose of this chapter is threefold.First, we discuss the recent advances in economics, statistics and econometrics that have been essential for the research presented in this volume. In particular, we consider analysis of trade union behaviour and bargaining models, as well as cointegration and error correction.Second, we present a selective survey of the literature on wage determination, with emphasis on studies applying bargaining models.Third, we briefly summarize Chapters 2-5.
URN:NBN:fi:bof-201408071720
Keywords: 330